Establishment of Moda De Moderna Bayong in Riverside,Commonwealth Quezon City - Alevio, Lyca M.; Alvarido, Jonalyn B.; Esto, Jeann; Enting, Arvie S.; Soberano, Maricar O. (2024)
This study provides a starting point for further research imo the lives of studen purentur and their challenges. Fature researchers are encouraged to build upon these findings to develop a deeper understanding of this demographic and promote awareness of the obstacles student parents encounter By addressing the idemified challenges through targeted supporn and institutional policies, stakeholders can facilitate a more imchasive and supportive educational environment for student-parents, ultimately enhancing their academic success and personal well-boing.
b